AN INVESTIGATION ON RC HIGH-RISE STRUCTURES WITH AND WITHOUT OUTRIGGERS UNDER LATERAL STATIC LOADS - Dedeoglu, Ibrahim Ozgur; Calayir, Yusuf; Arisoy, Bengi (Yildiz Technical Univ, 2020)
Today, the need of high-rise structures is rising throughout the world day by day. The package programs used in the modelling and analyzing of high structures are being renewed and improved every day. However, analytical solutions are still to be very helpful in the preliminary design of the building model. In this study, the analytical solution approach has assessed for the horizontal displacement determinations of the shear wall-framed systems and shear wall-framed systems with outrigger systems under the static horizontal loads. For this purpose, two building models with 45 floors have been considered. The shear wall-framed system with outriggers has created by adding outrigger system to the shear wall -framed system in two levels. As the horizontal loads to the building models, the triangular distributed load representing the earthquake load and the uniformly distributed load representing the wind load have been applied. Displacement solutions of both models under horizontal loads have been performed using the analytical approach and ETABS program. The results of both models have been compared with each other and the validity of analytical solutions have been evaluated. Internal forces occurred in the both models under horizontal loads have been also assessed. The internal force solutions were obtained by using ETABS program. In addition, the effectiveness of the outrigger system has been examined.
Keywords: RC high-rise structures; shear wall-framed system; outriggers; horizontal displacements; internal forces